Overview of Knowledge and Dietary Compliance in Patients Undergoing Hemodialysis at Santa Elisabeth Hospital Medan in 2025 - Magda Siringo-ringo; Rusmauli Lumban Gaol; Gryttha Tondang; Ruri Meilyana Tarigan (CV. ALIM'SPUBLISHING, 2026)
Chronic kidney disease is one of the global health problems that requires long-term therapy, one of which is through hemodialysis. According to the World Health Organization (WHO), adherence to treatment and diet is a key factor in improving the quality of life for patients with chronic diseases. An appropriate diet plays an important role in controlling electrolyte levels, fluids, and toxic substances in the body. This study aims to describe the knowledge and dietary compliance of patients undergoing hemodialysis at Santa Elisabeth Hospital Medan in 2025.This research used a descriptive quantitative design with a cross-sectional approach. The sample consisted of 36 patients selected using purposive sampling techniques. The research instrument was a questionnaire developed based on dietary guidelines for hemodialysis patients according to WHO and the Indonesian Ministry of Health standards. The results showed that among the 36 hemodialysis patients, 15 respondents (41.7%) had a good level of knowledge, 14 respondents (38.9%) had a moderate level, and 7 respondents (19.4%) had a low level of knowledge. Regarding dietary compliance, 13 respondents (36.1%) were compliant, 18 respondents (50.0%) were moderately compliant, and 3 respondents (13.9%) were non-compliant. There was a tendency showing that higher knowledge levels were positively correlated with better dietary compliance, in line with WHO’s principle that health education is an essential intervention in managing chronic diseases. This study recommends strengthening ongoing educational programs by healthcare professionals, particularly in delivering accurate and easy-to-understand information about diet management for hemodialysis patients.